2008
DOI: 10.1089/ten.tea.2007.0247
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte Production in Mass Suspension Culture: Embryonic Stem Cells as a Source for Great Amounts of Functional Cardiomyocytes

Abstract: Exploiting embryonic stem cell (ESC)-derived cardiomyocytes as a vital source for cell therapies and tissue engineering will depend on robust, large-scale production processes. Recently, we have reported stirring-controlled formation of embryoid bodies, enabling the generation of pure cardiomyocytes in 2-L scale. Expansion and differentiation of genetically engineered mouse ESCs was followed by antibiotic-based cardiomyocyte enrichment. Here we have investigated modification of various parameters aiming at pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 56 publications
0
30
1
Order By: Relevance
“…It was subsequently demonstrated that aggregate formation could be controlled by optimizing stirring conditions, specifically examining impeller type and stirring speed (Schroeder, Niebruegge et al 2005;Niebruegge, Nehring et al 2008). To purify the heterogeneous differentiating cultures for cardiomyocytes and to deplete undifferentiated cells, a genetic selection technique was used (Klug, Soonpaa et al 1996;Li, Pevny et al 1998;Marchetti, Gimond et al 2002;Zandstra, Bauwens et al 2003), whereby ESCs were genetically engineered to be neomycin resistant upon expression of myosin heavy chain (MHC).…”
Section: Scalable Production Of Hpsc-derived Cardiomyocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was subsequently demonstrated that aggregate formation could be controlled by optimizing stirring conditions, specifically examining impeller type and stirring speed (Schroeder, Niebruegge et al 2005;Niebruegge, Nehring et al 2008). To purify the heterogeneous differentiating cultures for cardiomyocytes and to deplete undifferentiated cells, a genetic selection technique was used (Klug, Soonpaa et al 1996;Li, Pevny et al 1998;Marchetti, Gimond et al 2002;Zandstra, Bauwens et al 2003), whereby ESCs were genetically engineered to be neomycin resistant upon expression of myosin heavy chain (MHC).…”
Section: Scalable Production Of Hpsc-derived Cardiomyocytesmentioning
confidence: 99%
“…This technique has been demonstrated to efficiently enrich mESC-derived cardiomyoyctes to greater than 70% in the stirred suspension system (Zandstra, Bauwens et al 2003). Improved culture homogeneity has not only been achieved via stirring, but also by incorporating a settling tube to separate EBs from the culture medium which permitted continuous medium perfusion thereby preventing wide variations in medium component concentrations including glucose and lactate (Bauwens, Yin et al 2005;Niebruegge, Nehring et al 2008). Additionally, by implementing direct control of dissolved oxygen concentration in a bioreactor system, improved cardiomyocyte yields per input ESC have been observed under hypoxic conditions (Bauwens, Yin et al 2005).…”
Section: Scalable Production Of Hpsc-derived Cardiomyocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers employ a myriad of aggregation methods for EB formation which promote natural aggregation or artificially force cell-cell interactions, such as rotary mass suspension (Abilez et al 2006;Niebruegge et al 2008) or microwell centrifugation (Burridge et al 2007;Moeller et al 2008), respectively. Many differences exist between methods regarding aggregation efficiency (Carpenedo et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Current methods for cardiac differentiation comprise the formation of embryoid bodies (EBs; [65]), 2D-culture (on Matrigel or Geltrex [59•, 63, 66]), or the inductive coculture feeder cells (END-2 stromal cells; [67]) that secrete signaling molecules. Generation of embryoid bodies can be achieved using (i) the hanging drop method [58] that is very laborious and only feasible for small amounts of cells, (ii) forced aggregation in micro-cavities [68], which lead to EBs of uniform size and shape, but is also limited in terms of throughput, and (iii) suspension culture ( [69]; own lab experience) that allows large scale production [70]. Most currently used protocols use direct differentiation of PSC in the monolayer format [59•, 62••] that does not require the formation of EBs and thereby reduces the procedural steps.…”
Section: Cardiac Differentiation Of Pluripotent Stem Cellsmentioning
confidence: 99%